Re-thinking Contemporary Political Behaviour The Difference that Agency Makes - Sadiya Akram (2019)
Proposing a novel approach to understanding the contemporary political landscape, Akram draws on the work of Pierre Bourdieu and Margaret Archer on agency and argues the need for an in-depth engagement with concepts of agency to improve the reach and scope of political analysis.